PENDAMPINGAN MASYARAKAT DALAM PERLINDUNGAN HUKUM KEKAYAAN INTELEKTUAL KOMUNAL GUNA PELESTARIAN KEARIFAN LOKAL DI DESA BATU BERIGA - Kusuma, winanda; permatasari, bunga; Yokotani, Yokotani (Universitas Mataram, 2024)
The Bangka Belitung Islands Province has a lot of communal intellectual property. One form of communal wealth is in the form of sea taber ritual ceremonies and sea alms which are part of traditional cultural expressions. The ritual ceremony of sea taber and almsgiving is owned by Batu Beriga Village, located in Central Bangka Regency. The sea taber and sea alms ritual activities are always carried out every year by the Village Government and attended by the local community and people on Bangka Island. Unfortunately, village communities do not yet know the importance of protecting communal intellectual property, even though the Copyright Law has provided protection for communal intellectual property. The aim of this community service is to raise awareness in the Batu Beriga Village community of the importance of legal protection for communal intellectual property and to preserve local wisdom, especially the village's traditional cultural expression in the form of the sea taber ritual. The implementation of this community service activity uses several stages. The first stage is outreach to village officials about the importance of legal protection of village communal intellectual property. The second stage is documentation of the implementation of sea taber and sea alms activities. The third stage involved compiling a book about the ritual of sea taber and sea alms in Batu Beriga Village. The results of community service activities are an increase in the understanding of the Batu Beriga village community about the forms of communal intellectual property. The public knows that regulations regarding EBT are regulated in Government Regulation Number 56 of 2002 concerning Communal Intellectual Property. Based on this PP, forms of Communal Intellectual Property include traditional cultural expressions, traditional knowledge, genetic resources, indications of origin, and potential geographical indications. Furthermore, there has been an increase in village community awareness to legally protect village-owned communal intellectual property. This effort can be carried out by the community by submitting an application to the local government to be registered as EBT. Carrying out activities to increase awareness of village officials, community leaders and also the community to protect the communal intellectual property owned by Batu Beriga, and compiling a book about sea taber.